REQUESTS IN LEARNERS’ DICTIONARIES: THEIR ROLE IN FOREIGN LANGUAGE USERS’ PRAGMATIC COMPETENCE AND META-PRAGMATIC AWARENESS - Safont, Maria Pilar; Campoy, Mari Carmen (ELIA: Estudios de Lingüística Inglesa Aplicada, 2017)
Abstract The purpose of this paper is to examine the presentation of request realisation strategies in three major learner dictionaries, namely the Longman Dictionary of Contemporary English (1995), the Collins Cobuild English Language Dictionary (1995) and the Oxford Advanced Learners Dictionary (1995). In so doing, we have followed research analysing pragmatic items in ELT materials (Boxer and Pickering, 1995; Meier, 1997; Alcón and Tricker, 2000), on the one hand, and studies on the presentation of pragmatic information in dictionaries (Zgusta, 1988; Nuccorini, 1993) on the other. Our analysis of request acts linguistic formulations in dictionaries was conducted on the basis of Trosborg’s taxonomies of request strategies and request head act modification (1995) and on Bardovi-Harlig and Hartford’s Maxim of congruence (1991). Results show that in line with previous studies on the presentation of pragmatic information in other ELT materials, dictionaries present pragmatic items without relating them to their actual context of language use. Furthermore, contrary to Nuccorini’s assumption (1993), we have found that information about request acts in dictionaries may not be wide enough for foreign language learners to promote their ability to use the target language appropriately.